Time, Income and Subjective Well-Being - 20 Years of Interdependent Multidimensional Polarization in Germany - Joachim Merz; Bettina Scherg (Institute of Labor Economics (IZA), 2021)
Society drifts apart in many dimensions. Economists focus on income of the poor and rich and the distribution of income but a broader spectrum of dimensions is required to draw the picture of multiple facets of individual life. In our study of multidimensional polarization we extend the income dimension by time, a pre-requisite and fundamental resource of any individual activity. In particular, we consider genuine personal time as a pronounced source of social participation in the sense of social inclusion/exclusion and Amartya Sen's capability approach. With an interdependence approach to multidimensional polarization we allow compensation between time and income, parameters of a CES-type subjective well-being function, where a possible substitution is evaluated empirically by the German population instead of arbitrarily chosen. Beyond subjective well-being indices we propose and apply a new intensity/gap measure to multidimensional polarization, the mean minimum polarization gap 2DGAP. This polarization intensity measure provides transparency with regard to each single attribute, which is important for targeted policies, while at the same time their interdependent relations is respected. The empirical investigation of interdependent multidimensional polarization incidence and intensity uses the German Socio-Economic Panel (GSOEP) and detailed time use diary data from the three German Time Use Surveys (GTUS) 1991/92, 2001/02 and the actual 2012/13. We focus on the working individuals where the working poor requires increasing interest in the economic and social political discussion. The microeconometric two-stage selectivity corrected estimation of interdependent multidimensional risk (incidence) and intensity quantifies socio-economic factors behind. Four striking results appear: First, genuine personal leisure time additional to income is a significant subjective well-being and polarization dimension. Second, its interdependence, its compensation/substitution, evaluated by the German Society, is of economic and statistical significance. Remarkably, besides compensation regimes, there are interdependent multidimensional polarization regimes where even higher income cannot compensate time deficits. Third, interdependent multidimensional polarization incidence (headcount ratio) decreased over those 20 years in Germany, however and in particular, as shown by the new minimum 2DGAP approach, interdependent multidimensional polarization intensity increased over those 20 years in Germany. Fourth, there are different multidimensional polarization results and developments for the poverty and affluence poles and regimes, for fulltime selfemployed, employees and subsequently for further socio-economic groups. And, polarization also appears with respect to social participation.
Keywords: I32; D31; J22; 330; 2001/02and 2012/13; two-stage Heckman estimates of polarization incidence and intensity; CES well-being function; interdependent multidimensional polarization; extended economic well-being; minimum multidimensional polarization intensity gap (2DGAP); satisfaction/happiness; life satisfaction; subjective well-being; time and income poverty and affluence; social participation; working poor and affluent; middle class; self-employment and employees; German Time Use Surveys 1991/92; German Socio-Economic Panel